Interactions between landscape structure and bird mobility traits affect the connectivity of agroecosystem networks - Jingjing Zhang (Elsevier, 2021)
Enhancing functional connectivity is key to achieving a sustainable agroecosystem. There has been an increase in using connectivity metrics to understand how spatial heterogeneity affects dispersal, yet most studies have been single-species focused. Variability in species’ ecological traits, such as movement ability, are predicted to interact with landscape configuration in determining connectivity. We used network analysis to evaluate the landscape connectivity fortwo native bird species with distinct dispersal abilities and habitat requirements in an agricultural landscape dominated by sheep and beef cattle farming in north Canterbury, New Zealand. Both bird species would have previously occupied this landscape and the recovery of their populations is desired; however, New Zealand pigeon/ kererū (Hemiphaga novaeseelandiae) is highly mobile, whereas the southern brown kiwi/ tokoeka (Apteryx australis) is flightless. We compared the connectivity properties, and network metrics between a more densely forested agricultural area and an adjacent area dominated by pastoral grassland. The primary contributors to the dispersal networks were the habitability of the matrix, size and spatial arrangement of vegetation patches, and the species’ gap-crossing ability. Tokoeka were able to utilise smaller patches as stepping-stones for dispersal, while kererū had larger home ranges and moved between more dispersed habitat patches. Several large forest patches were key in providing multiple and stronger links among habitat patches for both species. Our work suggests that one size does not fit all, rather, conservation strategies should account for multiple species’ life-histories and movement traits when creating connected ecological networks that comprise a functional agricultural landscape.